Basic electrical engineering - Cathey, Jimmie J.; Nasar, Syed A. (New Delhi Tata McGraw-Hill, 2010)
"Get complete coverage of Oracle E-Business Suite's Self-Service modules, including Oracle iProcurement, Oracle Internet Expenses, Oracle iSupplier Portal, and Oracle iReceivables, inside this Oracle Press guide. Oracle Self-Service Applications discusses the features of each module and how they benefit organizational workflow, and reviews common implementation considerations that apply to all the modules. The book also provides detailed configuration instructions explaining each screen and field"--
includes index
Keywords: Electrical engineering; Electronics